2019
DOI: 10.3390/cancers11111657
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antrodia cinnamomea Extract Reduced Cancer Stem-Like Phenotype Changes and Resensitized KRAS-Mutant Colorectal Cancer via a MicroRNA-27a Pathway

Abstract: Colorectal cancer (CRC) is one of the most common causes of death in Taiwan. Previous studies showed that Antrodia cinnamomea (AC) can treat poisoning, diarrhea, and various types of cancer. Therefore, we purified a novel ubiquinone derivative, AC009, and investigated its antitumor effects. Cell viability assays revealed that AC009 reduced the viability of several human CRC cell lines. AC009 treatment resulted in cell-cycle arrest/apoptosis, and these effects may occur via caspase and Bcl-2 signaling pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A purified derivative of maleic and succinic acid, YMGKI-1, was previously discovered in those ACM ethanolic extracts which have shown inhibition in the stemness of head and neck cancer initiating cells both in vitro and in vivo [ 12 ]. Despite the increasing evidence that AC has the capability to diminish the stemness of cancer initiating cells through modulating tumor miRNA expressions [ 13 , 14 , 15 ], there are still great challenges to translate in vivo findings into current human clinical trials endpoints [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A purified derivative of maleic and succinic acid, YMGKI-1, was previously discovered in those ACM ethanolic extracts which have shown inhibition in the stemness of head and neck cancer initiating cells both in vitro and in vivo [ 12 ]. Despite the increasing evidence that AC has the capability to diminish the stemness of cancer initiating cells through modulating tumor miRNA expressions [ 13 , 14 , 15 ], there are still great challenges to translate in vivo findings into current human clinical trials endpoints [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with our previous study, which showed that 4-AAQB suppressed tumorigenesis and inhibited cancer stem cell-like phenotype through multiple signaling pathways, including JAK-STAT and Wnt/β-catenin [ 17 ]. Moreover, literature demonstrated that 4-AAQB induced the apoptosis of CRC cells through the suppression of the Ras-signaling pathway via modulating the expression of cl-Caspase3/9 and cl-PARP [ 33 ]. Furthermore, few studies have reported that increased autophagy is associated with anti-EGFR drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effects were determined using lactate dehydrogenase (LDH) assay kits (Bio Vision Inc., Milpitas, CA, USA), following the manufacturer's instructions and descriptions from a previous study [35]. The cells were incubated with 4AAQB for 48 h, and the LDH release was determined based on the ratio of the medium-to-cell-lysate LDH activity.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%